E-188 Preoperative embolization in patients with hypervascular spinal metastases: a systematic review and meta-analysis. (23rd July 2022) - Soliman, M; Monteiro, A; Cappuzzo, J; Kuo, C; Aguirre, A; Baig, A; Khan, A; Jowdy, P; Pollina, J; Siddiqui, A; Mullin, J; Levy, E
Abstract : Introduction: Previous meta-analyses on the effect of preoperative embolization (PE) in spinal tumors surgery either included heterogenous spine tumors or were having many deficiencies (e.g. missing many studies). To our knowledge, this is the first metaanalysis to focus on comparing the outcomes of PE in hypervascular spinal metastasis. Methods: An extensive search of the literature describing PE embolization for hypervascular spine metastasis was conducted using the PubMed and EMBASE databases. Pooled odds ratio (OR) or standardized mean difference (SMD) with 95% confidence intervals were calculated via the random-effects model. We only included randomized controlled trials and cohort studies comparing PE and non-embolized patients. Results: Nine studies representing 239 patients with hypervascular spine metastasis met the inclusion criteria. The overall intraoperative (SMD=-0.741, 95%CI= -1.868;0.387) and perioperative blood loss (SMD=-0.873, 95%CI=-2.632;0.887), complications (OR=1.064, 95%CI=0.357;3.171), and operative time (SMD=-1.309, 95%CI=-4.188;1.571) were similar between the embolization and non-embolization groups. However, there was a significantly less blood transfusion requirement in the embolization group (SMD=-0.768, 95%CI=-1.230;-0.306). On metaregression and omitting Rehak et al.'s study, preoperative embolization was associated with a significant reduction in the intraoperative blood loss (SMD=-1.09, 95%CI=-1.94;-0.24). Conclusion: Preoperative embolization of hypervascular spine metastasis can effectively reduce intraoperative blood loss and blood transfusion requirement. Disclosures: M. Soliman: None. A. Monteiro: None. J. Cappuzzo: None. C. Kuo: None. A. Aguirre: None. A. Baig: None. A. Khan: None. P. Jowdy: None. J. Pollina: 2; C; ATEC Spine. 3; C; Medtronic. 4; C; REMI. 6; C; Royalty in ATEC spine. A. Siddiqui: 2; C; Amnis Therapeutics, Apellis Pharmaceuticals, Inc., Boston Scientific, Canon Medical Systems USA, Inc., Cardinal Health 200, LLC, Cerebrotech Medical Systems, Inc., Cerenovus, Cerevatech Medical, Inc. 4; C; Adona Medical, Inc., Amnis Therapeutics, Bend IT Technologies, Ltd., BlinkTBI, Inc, Buffalo Technology Partners, Inc., Cardinal Consultants, LLC, Cerebrotech Medical Systems, Inc, Cerevatech Medical. J. Mullin: 1; C; Cerapedics, AO Spine, Medtronic. E. Levy: 2; C; Claret Medical, GLG Consulting, Guidepoint Global, Imperial Care, Medtronic, Rebound, StimMed, Misionix, Mosiac, Clarion, IRRAS.. 4; C; NeXtGen Biologics, RAPID Medical, Claret Medical, Cognition Medical, Imperative Care, Rebound Therapeutics, StimMed, Three Rivers Medical.